Faktor yang Mempengaruhi Kunjungan Ibu Membawa Balita ke Posyandu Desa Gampa, Kabupaten Aceh Barat - Handayani, Ade Lia; Khairunnas, Khairunnas; Muliadi, Teuku; Alamsyah, T. (Polyscopia, 2024)
The participation of mothers with toddlers in Posyandu (Integrated Health Service Post) activities is essential for monitoring children's growth, health, and nutrition through regular weighing with the Towards Health Card (KMS). In 2020, only 43.3% of toddlers in West Aceh were weighed, with Puskesmas Johan Pahlawan recording just 13.9% in 2023, and Gampa Village showing only 0.15% from July to September. This study aimed to identify factors influencing mothers' visits to Posyandu in Gampa Village, West Aceh District. Using a descriptive correlation method with a cross-sectional design, 125 mothers with toddlers were selected from a population of 358 through accidental sampling. Data were collected via questionnaires and analyzed using the Chi-Square test. Significant relationships were found between Posyandu visits and education (p = 0.046), knowledge (p = 0.041), and family support (p = 0.003), while no significant relationships were observed for occupation (p = 0.337) and distance to Posyandu (p = 0.773). Strengthening counseling and socialization efforts is recommended to improve maternal awareness of the importance of regular Posyandu attendance for children's growth and development monitoring.